Zonula occludens proteins and their impact on the cancer microenvironment - Min-Hye Kim; Hee-Jae Cha (Kosin Medical Journal)
Zonula occludens (ZO) proteins serve as scaffolding proteins that provide structural support at cell junctions and the cytoplasmic surface, acting as bridges between integral membrane proteins and the cytoskeleton. In addition to their structural functions, they also regulate cell growth and proliferation. Recent studies have shown that ZO proteins are involved in various diseases, including cancer. Specifically, ZO proteins influence the growth and development of cancer cells in the tumor microenvironment. These proteins perform various functions in the tumor microenvironment through processes such as angiogenesis, inflammatory responses, epithelial-mesenchymal transition, and interactions with mesenchymal stem cells. The mechanisms of these actions may vary depending on the type of cancer and environmental conditions. Ongoing research explores several signaling pathways involving ZO proteins. These insights suggest that new therapeutic approaches may be considered to slow down cancer growth and development within the tumor microenvironment. Despite continuing research on the cellular and in vivo roles of ZO proteins, the current understanding of how these signaling mechanisms function within the tumor microenvironment in vivo remains limited. In this review, we introduce the characteristics and regulatory mechanisms of ZO proteins in the cancer microenvironment, explore their potential to suppress cancer cell environments, and examine their roles in vivo.